Dark future : uncovering the Great Reset's terrifying next phase - Beck, Glenn; Haskins, Justin (Director of the Stopping Socialism Center) (Beck, Glenn. Great Reset series., 2023)
Beck and Haskins reveal the most important technologies and social and cultural changes that will soon cause an unprecedented level of disruption in the United States, as well as in countless other nations. Elite radicals are plotting to seize increasingly more power for themselves and the institutions they control using emerging technologies: artificial intelligence, central bank digital currencies, brain implants, and even gene editing and bioengineering. Here Beck and Haskins provide the information readers need to plan for the dramatic technological changes that are headed their way within the next decade. -- adapted from jacket